2010
DOI: 10.1016/j.metabol.2009.07.014
|View full text |Cite
|
Sign up to set email alerts
|

Acute altitude-induced hypoxia suppresses plasma glucose and leptin in healthy humans

Abstract: To examine the effects of acute altitude-induced hypoxia on the hormonal and metabolic response to ingested glucose, 8 young, healthy subjects (5 men/3 women; 26±2 yrs; BMI, 23.1±1.0 kg/m2) performed two randomized trials in a hypobaric chamber where a 75 g glucose solution was ingested under simulated altitude (ALT, 4,300m), or ambient (AMB, 362m) conditions. Plasma glucose, insulin, c-peptide, epinephrine, leptin and lactate concentrations were measured at baseline and 30, 60, 90 and 120 min after glucose in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
54
2
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 62 publications
(61 citation statements)
references
References 39 publications
3
54
2
2
Order By: Relevance
“…Similar to the effects of exercise, increased epinephrine during IHE, which was reported in healthy humans may have contributed to glycogen utilization via increases in cyclic adenosine monophosphate concentrations, potentially leading to post-treatment increased on insulin sensitivity [72].…”
Section: Intermittent Hypoxia and Insulin Sensitivitymentioning
confidence: 71%
See 1 more Smart Citation
“…Similar to the effects of exercise, increased epinephrine during IHE, which was reported in healthy humans may have contributed to glycogen utilization via increases in cyclic adenosine monophosphate concentrations, potentially leading to post-treatment increased on insulin sensitivity [72].…”
Section: Intermittent Hypoxia and Insulin Sensitivitymentioning
confidence: 71%
“…Other trial 12 demonstrated that IHE glucose tolerance enhancement four hours after exposure can be attributed to improvements in peripheral insulin sensitivity in sedentary males with T2D. Therefore, it may improve short-term glycaemic control [85].Similar to the effects of exercise, increased epinephrine during IHE, which was reported in healthy humans may have contributed to glycogen utilization via increases in cyclic adenosine monophosphate concentrations, potentially leading to post-treatment increased on insulin sensitivity [72].Similarly, it has been described that both IHE and IHT programmes carried out in hypoxic conditions increased glucose transporter GLUT-4 levels [33].Hypoxia and exercise have shown an additive effect on insulin sensitivity [87], suggesting that insulin signalling and insulin-dependent glucose transport, might have been up-regulated following hypoxic exercise [33, 34]. This additive improvement could also be attributed to an increase in the relative intensity of the practised exercise in hypoxia [56].…”
mentioning
confidence: 91%
“…In healthy subjects, acute exposure to high altitude ≥3000m resulted in a reduction in insulin sensitivity in some studies [10][11][12][13][14], although glucose metabolism was enhanced, as shown in two studies [9,15] that reported a 36%-60% improvement in glucose uptake. Chronic exposure of ≥21 days, at moderate levels of altitude (1,700m-2740m) [6,9] demonstrated improvements in fasting glucose levels [6,9].…”
Section: Blood Glucosementioning
confidence: 96%
“…It would also suggest that patients with issues with blood regulation should monitor their blood glucose status when participating in hypoxic training involving high exercise intensities or high levels of hypoxia. Secretion of epinephrine has been suggested to be responsible for the rise in blood glucose levels and reduction in insulin sensitivity [14,15], however in one study, epinephrine levels remained unchanged despite a rise in blood glucose, indicating alternative metabolic signalling pathways [17]. Additionally hormones such as oestrogen may affect the response to hypoxic training as seen with gender differences in glucose response to hypoxic training [17].…”
Section: Blood Glucosementioning
confidence: 98%
See 1 more Smart Citation